Construções relacionais de fingimento com os verbos "pagar" e "dar" - Rodrigues Pinto, Kátia Roberta (2021)
Based on Usage-based Model’s theoretical and methodological assumptions (KEMMER; BARLOW, 2000; BYBEE, 2010), and focusing on Construction Grammar principles (GOLDBERG, 1995; 2006), this dissertation aims to describe the form-meaning pairing of constructions that denote pretending of state, being those with the verbs "pagar" (to pay) and "dar" (to give). The specific objectives are: (i) to characterize such constructions in terms of schematicity, productivity and compositionality (TRAUGOTT; TROUSDALE, 2021), (ii) to distinguish microconstructional patterns and (iii) to determine their hierarchical and inheritance relationships within the broader network of relational constructs. Adopting parameters that map both formal and semantic-pragmatic aspects of these constructions, it is possible to achieve results that point to constructional patterns instantiated by two subschemas, a subscheme of durative pretending, Subj+[Vrel]+de+Np/Adjp, a subscheme of punctual pretending, Subj+[Vrel]+uma+de+ Np/Adjp, which can be further divided into four micro-constructions, represented as follows: Subj+pagar+de+Np/Adjp; Subj+dar+de+Np/Adjp, Subj+pagar+uma+de+Np/Adjp e Subj+dar+uma+de+Np/Adjp. For this purpose, the Web Dialects section of the Corpus do Português (DAVIES; FERREIRA, 2006) database was used. It is argued that the state pretending constructions belong to the relational constructions network, whose most prototypical members are the state constructions with verbs "ser" and "estar" (to be in English) (FERREIRA, 2015). The constructions of pretending of state with "pagar" and "dar" are marginal members of this network, since, while they share certain features with the prototype members, such as relational meaning and condition of the individual's state, they also distance themselves from them by presenting some distinct properties, including agent subject and dysphoric pragmatic nature.